2021
DOI: 10.1111/aogs.14129
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of immediate postpartum and post‐abortion long‐acting reversible contraception provision to adolescents: A systematic review

Abstract: Introduction Long‐acting reversible contraception (LARC) methods are safe for adolescents and provide the greatest assurance against rapid repeated pregnancy when inserted during the immediate postpartum (IPP) and immediate post‐abortion (IPA) period. Despite increasing enthusiasm for IPP/IPA LARC insertion, adolescents’ preferences and experiences have seldom been examined. The objective of this review was to examine the attitudes of adolescents (aged 10–19 years) towards IPP/IPA LARC, their experiences and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In contrast with other reviews,21–24 this paper focuses on women’s perspectives from high-income countries. Other reviews have focused on specific demographic groups such as adolescents,21 22 low-income countries23 24 or individual methods of contraception 21.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast with other reviews,21–24 this paper focuses on women’s perspectives from high-income countries. Other reviews have focused on specific demographic groups such as adolescents,21 22 low-income countries23 24 or individual methods of contraception 21.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with other reviews,21–24 this paper focuses on women’s perspectives from high-income countries. Other reviews have focused on specific demographic groups such as adolescents,21 22 low-income countries23 24 or individual methods of contraception 21. These reviews demonstrated that patient education, including a higher level of education achievement,21 24 and specific contraception education,22–24 increases contraception uptake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 Immediate postabortion LARC insertion is generally acceptable to adolescents and nulliparous women, although rates of LARC uptake in these groups may be lower than in parous and adult women. 71 , 72 Importantly, immediate LARC initiation does not increase the risk of medication-induced abortion failure. 73 Rates of IUD complications and expulsions following first-trimester uterine aspiration and medication-induced abortions are low.…”
Section: Larc Uptake Continuation and Barriers To Usementioning
confidence: 99%